2023
DOI: 10.1177/03635465221138548
|View full text |Cite
|
Sign up to set email alerts
|

Fibular- Versus Tibiofibular-Based Reconstruction of the Posterolateral Corner of the Knee: A Systematic Review and Meta-analysis

Abstract: Background: Fibular- and tibiofibular-based reconstructions are the gold standard treatment for posterolateral corner (PLC) injuries of the knee. Despite comparable outcomes in biomechanical studies, clinical results comparing these constructs remain elusive with no consensus reached regarding the best treatment option. Purpose: To perform a systematic review and meta-analysis to compare fibular- and tibiofibular-based techniques for posterolateral corner reconstruction. We aimed to identify whether any differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 54 publications
1
17
0
Order By: Relevance
“…They concluded, however, that higher quality studies are required to reinforce or refute such conclusions because most of the studies in this review were of poor-to-fair quality. 38 Dekker et al 39 in their retrospective study found no difference in laxity or clinical outcomes in patients having LCL reconstructions when comparing autografts and allografts. The extra-articular nature of the PLC makes allograft a reasonable option, barring their availability.…”
Section: Reconstructionmentioning
confidence: 92%
See 2 more Smart Citations
“…They concluded, however, that higher quality studies are required to reinforce or refute such conclusions because most of the studies in this review were of poor-to-fair quality. 38 Dekker et al 39 in their retrospective study found no difference in laxity or clinical outcomes in patients having LCL reconstructions when comparing autografts and allografts. The extra-articular nature of the PLC makes allograft a reasonable option, barring their availability.…”
Section: Reconstructionmentioning
confidence: 92%
“…They concluded, however, that higher quality studies are required to reinforce or refute such conclusions because most of the studies in this review were of poor-to-fair quality. 38…”
Section: Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Particularly in the revision setting, the patient should be made aware of the possibility of arthrofibrosis, graft failure, and the occurrence or persistence of peroneal nerve symptoms. 2,5,7,9…”
Section: Video Transcriptmentioning
confidence: 99%
“…However, non‐operative management for grade III PLC injuries have been reported to result in inferior functional outcomes, persistent instability, and the development of early‐onset degenerative changes [12, 26]. As a result, a variety of repair and reconstruction techniques have evolved to restore knee stability [1, 3, 8, 13, 16, 35, 37, 43, 47, 49, 53, 55, 56]. Despite considerable attention in the recent orthopaedic literature, optimal timing of surgery and the ideal surgical treatment option remains controversial for these complex injuries [6].…”
Section: Introductionmentioning
confidence: 99%